Inferences Based on Robust Regression Estimators When There Is Multicolinearity - Wilcox, Rand (Advances in Social Sciences Research Journal, 2018)
The paper deals with the goal of testing hypotheses about the slope parameters of a linear regression model when there is multicolinearity. A heteroscedastic method was recently derived based on a ridge estimator, but it does not guard against the deleterious impact of outliers. Several robust analogs of the ridge estimator have been proposed that might deal with this concern. The goal here is to find a robust method that performs reasonably well in simulations.